Comparison of Integrated Pest Management Knowledge, Attitude, and Practice among staff members of Four Major Hospitals in Benghazi - H. Elmhalli, Fawzeia; S. Garboui, Samira; H. Ibrahim, Naser; N. Ali, Rania; A. Awad, Faiza; A. Ibrahim, Yasmine (Libyan Journal of Public Health Practices, 2024)
Pests in the hospital environment pose a significant risk to the safety of patients and staff. While pesticides are commonly used to control pests, they can lead to additional problems. Therefore, alternative procedures such as Integrated Pest Management (IPM) have gained attention. This study aimed to assess hospital staff knowledge, practice, and attitudes regarding IPM in four major hospitals in Benghazi. A cross-sectional study used a questionnaire and checklist to collect the data from the participants. The results indicated that all hospitals showed low IPM knowledge and practiced widespread pesticide use. The Surgical and Emergency Hospital (SEH) demonstrated significantly higher IPM knowledge, practice, and attitude scores than the other three hospitals (p = 0.000), with a mean of 4.56, 2.61, and 10.94, respectively. All studied hospitals experienced pest infestations such as houseflies and roaches. These hospitals rely mainly on chemical control, employing 14 types of pesticides, including five restricted-use pesticides and seven that are banned. In addition, these chemicals can be used without proper supervision and by uncertified users with limited knowledge.